Faktor-Faktor yang Mempengaruhi Perilaku Petani dalam Penggunaan Pestisida dan Peran Stakeholders dalam Pengelolaannya di Kabupaten Solok Sumatera Barat - Friska Eka Fitria; Ade Suzana Eka Putri; Eria Azzahra Hadi (Jurnal Kesehatan Komunitas, 2026)
The unsafe and unhealthy use of pesticides by farmers is still a public health problem in agricultural areas, but comprehensive studies that reveal farmer behavior factors and the role of stakeholders in pesticide management are still limited, especially in horticultural centers such as Solok Regency. This study aims to explore the factors that influence farmers' behavior in pesticide use and analyze the role of stakeholders in its management, so that strategic recommendations for pesticide use can be formulated. The study uses a qualitative design with a case study approach in Solok Regency, West Sumatra, from March to July 2025. Informants in this study were selected using purposive sampling, consisting of nine independent farmers and eleven group farmers as key informants, as well as nine stakeholders as supporting informants. Data were collected through FGDs and in-depth interviews, analyzed using content analysis, and validated using source and method triangulation. The results showed that farmers' behavior in pesticide use was influenced by their perception of pesticides as a guarantee of successful harvests, concerns about yield decline, and economic constraints. In addition, weak supervision and cross-sector coordination by the Fertilizer and Pesticide Supervisory Commission (KPPP), the limited role of extension workers and health workers, and suboptimal access to personal protective equipment weaken the cues to action for farmers. This study concludes that changing behavior towards safe and healthy pesticide use requires comprehensive interventions that integrate a behavior change approach based on the Health Belief Model with the strengthening of supervision systems, extension services, and collaboration among relevant stakeholders. Keywords : pesticide use, farmers’ behavior, stakeholders